Analysis on Portfolio Assessment Leadership Management in Universitas PGRI Palembang - Lestari, Neta Dian; Rachmawati, Diana Widhi; Yusmiono, Boby Agus (Graduate Program Magister Manajemen Pendidikan, 2021)
Portfolio assessment is an approach that is not new anymore, portfolios are exposed by educational experts to be implemented in educational institutions. In addition to the new assessment approach, the old portfolio assessment approach can be used. The application of portfolio assessment has not been optimally applied to learning activities in Higher Education. Research objectives were to analyze the application of portfolios in Leadership Management courses in the Primary School Teacher Education Study Program Universitas PGRI Palembang. We used descriptive method. The results of data analysis carried out in the study concluded that the application of the portfolio was very good in terms of student activity in learning, assignments and final test results in the Very Active or Very Good categories. Learning activities were 51.61% very active, 38.71% very good assignments and the final test was 54.84% very good. Based on the results of this study, the application of portfolio assessment is expected to be an alternative strategy for educators in the learning process to improve learning outcomes, motivate learning and as an effort to improve the quality of student learning.